Social studies in elementary education - Jarolomek, John (MacMillan, 1993)
For preservice, inservice, and graduate courses on social studies in elementary education. More practical than ever, this number one text retains the clarity and friendly tone of previous editions while taking a fresh look at diversity, technology, democratic citizenship, and expanding social studies across the curriculum. It details the mission of social studies education, considers the diversity of children in today's social studies classrooms, addresses the social studies curriculum, and explores effective instruction. The author continues the tradition of applying educational concepts with specific classroom examples and field-tested lesson plans in this classic.